Molecular Diagnostics in Urologic Malignancies. - Netto, George J. (Archives of Pathology & Laboratory Medicine, 2011)
Context.-Molecular diagnostic applications are now an integral part of the management algorithms of several solid tumors, such as breast, colon, and lung. In stark contrast, the current clinical management of urologic malignancies is lagging behind. Clinically robust molecular tests that can identify patients who are more likely to respond to a given targeted agent or even those in need of a more aggressive treatment based on well-validated molecular prognosticators are still lacking. Several promising biomarkers for detection, prognosis, and targeted therapeutics are being evaluated. Objective.-To discuss candidate biomarkers that may soon make the transition to clinical assay for patients in urologic oncology. Data Sources.-Selected original articles published in the PubMed service of the US National Library of Medicine. Conclusions.-Recent understanding of the complex molecular alterations involved in the development and progression of urologic malignancies is yielding novel diagnostic and prognostic molecular tools and opening the doors for experimental targeted therapies in these prevalent, frequently lethal solid tumors.